Prevalence of Cardiac Sarcoidosis in Middle-Aged Adults Diagnosed with High-Grade Atrioventricular Block - Maizels, Leonid; Mansour, Mahmoud; Abu-Much, Arsalan; Massalha, Eias; Kalstein, Maia; Beinart, Roy; Sabbag, Avi; Brodov, Yafim; Goitein, Orly; Chernomordik, Fernando; Berger, Michael; Herscovici, Romana; et al. (The American journal of medicine, 2024)
Atrioventricular block may be idiopathic or a secondary manifestation of an underlying systemic disease. Cardiac sarcoidosis is a significant underlying cause of high-grade atrioventricular block, posing diagnostic challenges and significant clinical implications. This study aimed to assess the prevalence and clinical characteristics of cardiac sarcoidosis among younger patients presenting with unexplained high-grade atrioventricular block. We evaluated patients aged between 18 and 65 years presenting with unexplained high-grade atrioventricular block, who were systematically referred for cardiac magnetic resonance imaging, positron emission tomography-computed tomography, or both, prior to pacemaker implantation. Subjects with suspected cardiac sarcoidosis based on imaging findings were further referred for tissue biopsy. Cardiac sarcoidosis diagnosis was confirmed based on biopsy results. Overall, 30 patients with high-grade atrioventricular block were included in the analysis. The median age was 56.5 years (interquartile range 53-61.75, years). In 37%, cardiac magnetic resonance imaging, positron emission tomography-computed tomography, or both, were suggestive of cardiac sarcoidosis, and in 33% cardiac sarcoidosis was confirmed by tissue biopsy. Compared with idiopathic high-grade atrioventricular block patients, all cardiac sarcoidosis patients were males (100% vs 60%, P = .029), were more likely to present with heart failure symptoms (50% vs 10%, P = .047), had thicker inter-ventricular septum on echocardiography (12.2 ± 2.7 mm vs 9.45 ± 1.6 mm, P = .002), and were more likely to present with right ventricular dysfunction (33% vs 10%, P = .047). Cardiac sarcoidosis was confirmed in one-third of patients ≤ 65 years, who presented with unexplained high-grade atrioventricular block. Cardiac sarcoidosis should be highly suspected in such patients, particularly in males who present with heart failure symptoms or exhibit thicker inter-ventricular septum and right ventricular dysfunction on echocardiography.